Bone grafting technique to increase interdental alveolar bone height for placement of an implant - M. Fukuda,* T. Takahashi, T. Yamaguchi (Blackwell Synergy, 2000)
One of the main problems with endosseous implants is insufficient width or height or both of the alveolar ridge at the implantation site. Several techniques of bone grafting have been proposed to solve the problem. 1 Although chin bone onlay grafting is a well established way of widening the narrow maxillary ridge, to our knowledge it has not been used to increase interdental alveolar bone height. We report a technique to increase bone height by chin bone onlay grafting in conjunction with placement of the implant.